2017
DOI: 10.1007/s00267-017-0890-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Climate Compatible Development Outcomes and their Implications for Distributive Justice: Evidence from Malawi

Abstract: Governments and donors are investing in climate compatible development in order to reduce climate and development vulnerabilities. However, the rate at which climate compatible development is being operationalised has outpaced academic enquiry into the concept. Interventions aiming to achieve climate compatible development “wins” (for development, mitigation, adaptation) can also create negative side-effects. Moreover, benefits and negative side-effects may differ across time and space and have diverse consequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Dyer et al [16] observe that adequate participatory practices and community engagement, combined with establishment of successful multi-stakeholder partnerships, are key factors for project and policy objectives to be met. However, the capacity to set adequate objectives that address mitigation, adaptation and development is hampered by the difficulty in engaging locally to tailor actions that can address community-specific needs [17]. Focus on mitigation, adaptation and development dimensions varies across stakeholder groups at multiple levels, and there is a need to better understand how best to assess and integrate local-level perspectives into climate and development policy and practice.…”
Section: Introductionmentioning
confidence: 99%
“…Dyer et al [16] observe that adequate participatory practices and community engagement, combined with establishment of successful multi-stakeholder partnerships, are key factors for project and policy objectives to be met. However, the capacity to set adequate objectives that address mitigation, adaptation and development is hampered by the difficulty in engaging locally to tailor actions that can address community-specific needs [17]. Focus on mitigation, adaptation and development dimensions varies across stakeholder groups at multiple levels, and there is a need to better understand how best to assess and integrate local-level perspectives into climate and development policy and practice.…”
Section: Introductionmentioning
confidence: 99%
“…The projects professed to include particularly marginalized households in implementation (e.g., the extremely resourcepoor, elderly-headed, female-headed, those with disabled or chronically ill adult members) whose capacity to adapt to climate shocks and stresses is extremely low." 50 Some articles in this category focus on documenting evidence of risk reduction or reduced vulnerability, wherein marginalized groups are shown to successfully take up or benefit from adaptation responses.…”
Section: How Is Equity Integrated Into Adaptation?mentioning
confidence: 99%
“…Climate compatible development (CCD) refers to “development that minimizes the harm caused by climate impacts, while maximizing the many human development opportunities presented by a low‐emissions, more resilient future.” Examples of CCD in low‐ and middle‐income African countries may include improved cook stoves, installation of solar lights, and improved forestry and farming techniques . Investigators studying the adoption of CCD in three regions in Malawi identified that these programs could be successful, though not all were . On average, two to three benefits each were experienced by households, and wealthier, youth‐headed, and male‐headed households benefited more than others …”
Section: Development Versus Environmental Conservation and The Path Fmentioning
confidence: 99%
“…Investigators studying the adoption of CCD in three regions in Malawi identified that these programs could be successful, though not all were . On average, two to three benefits each were experienced by households, and wealthier, youth‐headed, and male‐headed households benefited more than others …”
Section: Development Versus Environmental Conservation and The Path Fmentioning
confidence: 99%